PENERAPAN TEOLOGI KESALEHAN YOHANES CALVIN DALAM KONTEKS JEMAAT GMIM:: SUATU KAJIAN TEOLOGI PRAKTIS - Wagania, Stevanoch Marcky; Tulangouw, Maria Elisa (Jurnal Teologi RAI, 2025)
This study aims to analyze the concept of piety in John Calvin’s theology and its implications for the life of the GMIM Efrata Wusa congregation. Piety is an important issue given the weak spiritual awareness of the congregation amid the pressures of modern life, which has caused prayer and worship practices to lose their deep meaning. Using theological literature study methods and field research in the form of interviews and observations of special ministers and congregations, this study found that Calvin’s teachings on prayer, repentance, self-denial, and obedience are highly relevant to restoring the spirituality of the congregation. Calvin viewed piety not merely as personal discipline but as a lifestyle rooted in the knowledge of God and manifested in real life. The GMIM Efrata Wusa congregation, in its confession, demonstrates openness to contextual and comprehensive spiritual formation. Therefore, Calvin’s understanding of piety can serve as a theological foundation for the renewal of spiritual life within the context of the local church today.